Does Abiotic Stress Cause Functional B Vitamin Deficiency in Plants? . Issue 4 (2nd November 2016) - Hanson, Andrew D.; Beaudoin, Guillaume A.; McCarty, Donald R.; Gregory, Jesse F.
Abstract : Unlike animals, plants produce their own B vitamins but may nonetheless suffer vitamin deficiencies under stress conditions, with wide-ranging metabolic consequences. Abstract: B vitamins are the precursors of essential metabolic cofactors but are prone to destruction under stress conditions. It is therefore a priori reasonable that stressed plants suffer B vitamin deficiencies and that certain stress symptoms are metabolic knock-on effects of these deficiencies. Given the logic of these arguments, and the existence of data to support them, it is a shock to realize that the roles of B vitamins in plant abiotic stress have had minimal attention in the literature (100-fold less than hormones) and continue to be overlooked. In this article, we therefore aim to explain the connections among B vitamins, enzyme cofactors, and stress conditions in plants. We first outline the chemistry and biochemistry of B vitamins and explore the concept of vitamin deficiency with the help of information from mammals. We then summarize classical and recent evidence for stress-induced vitamin deficiencies and for plant responses that counter these deficiencies. Lastly, we consider potential implications for agriculture.